The impact of forensic accounting in detecting financial fraud: A case study of private hospital in the city of Zakho - Mohammed, Kasar (Humanities Journal of University of Zakho, 2023)
The aim of this study is to demonstrate the impact of forensic accounting in detecting financial fraud to achieve the study objective; descriptive approach has been used for a case that occurred in one of a private hospital in Zakho city. For this purpose, an official letter has been presented from the presidency of the university to the Zakho Court to review the financial statements of the case which has been presented by the lawyer as evidence to proof the complaint. The account statements have revealed that the accused have manipulated the profits of the hospital during their work. We concluded that the forensic accounting play an important role in detecting financial fraud Therefore, this type of accounting is considered as an important tool because of its crucial role in detection of financial frauds. We recommend that concerned parties should train their staff to have an efficient knowledge in modern technique tools in the field of accounting and audit.